MUTU MIKROBIOLOGIS DRUPA BUAH MERAH (Pandanus conoideus Lamk.) PADA BERBAGAI JENIS KEMASAN SELAMA PENYIMPANAN - Mathelda Kurniaty Roreng; Zita Letviany Sarungallo; Murtiningrum Murtiningrum; Budi Santoso; Rossa MM Latumahina (AGROINTEK, 2016)
Microbiological quality is one crucial factor relating to food products quality. This quality can be measured based on the growth level of bacteria and fungi during storage of food product. The objective of this study is to determine the effect of plastic packaging types and different storage conditions on total bacteria and total fungi in fresh red fruit. The experiment was conducted using three treatments of plastic packaging, that is high-density polyethylene (HDPE), low density polyethylene (LDPE) and polypropylene (PP). Additionally, three storage conditions were applied, that is room temperature (27 °C), cold temperature (10 °C) and freezing temperatures (-18° C). The results showed that during storage, freezing conditions inhibited the growth of bacteria and fungi. Meanwhile, the type of plastic packaging did not inhibit the growth of bacteria and fungi.